Iron(III)-catalyzed conia–ene cyclization of 2-alkynic 1,3-dicarbonyl compounds - Chan, Li Yan (2013)
A cheap, simple, and effective FeCl3-catalyzed Conia–ene cyclization of 2-alkynic 1,3-dicarbonyl compounds was stereospecific to afford alkylidenecyclopentanes in (E)-isomers via the 5-exo-dig pathway. The 5-endo-dig and 6-exo-dig cyclizations were also possible, depending on the structure of the substrates.